(untitled) (World Economics and Finance Bulletin, 2023)
Historically, at each stage of economic development, the form of settlements and payment instruments has been changed in order to meet the requirements of society. The culmination of the changes caused by technological progress was the emergence of digital assets before the introduction of electronic money. It was found that even the low number of outlets that accept electronic and digital money as a means of payment does not allow them to become popular and expand the customer base of digital money systems.